Biological Effects of Thermal Water-Associated Hydrogen Sulfide on Human Airways and Associated Immune Cells: Implications for Respiratory Diseases - Viegas, Joana; Esteves, Ana Filipa; Cardoso, Elsa M.; Arosa, Fernando A.; Vitale, Marco; Taborda-Barata, Luís (Frontiers in Public Health, 2019)
Natural mineral (thermal) waters have been used for centuries as treatment for various diseases. However, the scientific background of such therapeutic action is mostly empiric and based on knowledge acquired over time. Among the various types of natural mineral waters, sulfurous thermal waters (STWs) are the most common type in the centre of Portugal. STWs are characterized by high pH, poor mineralization, and the presence of several ions and salts, such as bicarbonate, sodium, fluoride, silica, and carbonate. Furthermore, these waters are indicated as a good option for the treatment of various illnesses, namely respiratory diseases (e. g. allergic rhinitis, asthma, and chronic obstructive pulmonary disease). From the sulfide species present in these waters, hydrogen sulfide (H2S) stands out due to its abundance. In healthy conditions, H2S-related enzymes (e. g. cystathionine β-synthase and cystathionine -lyase) are expressed in human lungs, where they have mucolytic, antioxidant, anti-inflammatory, and antibacterial roles, thus contributing to airway epithelium homeostasis. These roles occur mainly through S-sulfhydration, a post-translational modification through which H2S is able to change the activity of several targets, such as ion channels, second messengers, proteins, among others. However, in respiratory diseases the metabolism of H2S is altered, which seems to contribute somehow to the respiratory deterioration. Moreover, H2S has been regarded as a good biomarker of airway dysfunction and severity, and can be measured in serum, sputum, and exhaled air. Hence, in this review we will recapitulate the effects of STWs on lung epithelial-immune crosstalk through the action of its main component, H2S.